(3TQM dGejI GdefWbs - (3CMeO Hf eMeO Hf jYbhH, CHh GdYHGS GdnhnqdGdj,J (B1128 (3g` s
(3ChdgG (B:s
(3hHYO abO cfJ ajeG eVi hVYJ dGejI GdefWb s
(3BNQgG (B:s
(3cGdefOjd hde jYde dg SGHb ajg Ydi gPG GdhLg s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B241 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B156s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRGhjg GdMeRGhjI (B_ (3GdeZQH (B(254) s
Keywords: (3GdadSaI hGdefWbs